Role of Vitamin B(6) Biosynthetic Rate in the Study of Vitamin B(6) Synthesis in Escherichia coli - Dempsey, Walter B. (1971)
Nutritional auxotrophs of Escherichia coli synthesize vitamin B(6) compounds at a rate of 1 × 10(−10) to 2 × 10(−10) moles per hr per mg (dry weight) of cells when they are suspended in minimal medium lacking their required nutrients. A few auxotrophs have been found to stop or reduce vitamin B(6) synthesis during such an experiment. These include thiamineless, citrate synthaseless, and pyridoxineless mutants as well as mutants which require four carbon compounds for growth. Glycolaldehyde was found to restore vitamin B(6) synthesis in the last named of these mutants without restoring normal growth. A class of pyridoxineless mutants which responded with normal growth to 0.4 mm glycolaldehyde or 0.15 × 10(−3) mm pyridoxol was also found. The results suggest that a thiamine pyrophosphate-requiring step as well as glycolaldehyde may be involved in pyridoxal phosphate biosynthesis.